Enhanced Efficiency Organo-Mineral Nitrogen Fertilizer improves Yield and Quality of Red Amaranth (Journal of Science and Technology Research, 2024)
Crop production with increased yield in a sustainable manner requires less environmental impact. Therefore, a pot experiment was accomplished to investigate the effect of newly developed enhanced efficiency nitrogen (N) fertilizer and conventional N fertilizers on the growth, yield, nutritional quality, and N use efficiency of red amaranth (Amaranthus tricolor cv. BARI lalshak 1). All the pots were placed at the experimental pot-house of the Department of Agricultural Chemistry, Bangladesh Agricultural University following a completely randomized design (CRD) with four replications. Brown coal-urea (BCU) was applied as enhanced efficiency N fertilizer following top dressing and basal application strategy where urea and diammonium phosphate were applied as conventional N fertilizer. All the N fertilizers were applied at five rates viz., 0, 50, 75, 100, 150 kg N ha ̶ 1. The growth parameters and biomass yield of red amaranth were significantly impacted by varying amounts and types of N fertilizers. The highest dry biomass yield was obtained at 150 kg N ha ̶ 1 whereas the highest number of branch plant ̶ 1 was found at 100 kg N ha ̶ 1. Again, the highest biomass N concentration was found at 100 kg N ha ̶ 1. Application of a higher dose of fertilizer showed the highest N concentration in the post-harvest soil. Overall, the growth parameters and biomass N concentration were the highest in BCU basal-treated soil. In contrast, BCU top-dressed soil showed a higher N concentration after harvest than all other treatments. Based on the overall findings, the use of higher-efficiency organo-mineral N fertilizer has the potential to serve as a viable substitute for traditional N fertilizers in the context of sustainable crop production with reduced environmental effects.J. of Sci. and Tech. Res. 5(1): 37-44, 2023